Magnolol and its semi-synthetic derivatives: a comprehensive review of anti-cancer mechanisms, pharmacokinetics, and future therapeutic potential - Asmita Rayamajhi; Nisha Gyawali; Deepa Karki; Luis E. Pérez-Caltzontzin; Sheila I. Peña-Corona; Hernán Cortés; Achyut Adhikari; Gerardo Leyva-Gómez; Yadav Uprety; Solomon Habtemariam; Lashyn Kiyekbayeva; Javad Sharifi-Rad (Discover Oncology)
Abstract In recent years, magnolol (MG), a natural active compound of polyphenolic nature, has garnered significant interest for its anti-cancer effects. Numerous studies conducted on cell lines and animal models have indicated a positive impact of administering drugs or semi-synthesized products derived from MG, including a decreased incidence of various cancers. This review aims to illustrate the underlying cellular and molecular basis of its actions. The article includes in-depth explanations of phytochemistry, semi-synthetic derivatives, bioavailability, pharmacokinetics, preclinical research, anti-tumor mechanisms, human clinical studies, toxicity, side effects, and safety. It also demonstrates that, in contrast to the wealth of synthetic medications, MG is highly effective against bladder, colon, gastric, skin, liver, lung, gallbladder, and prostate cancers. The findings of this review indicate that MG is a promising candidate as an anti-tumor agent, and future research should focus on developing new semi-synthetic derivative compounds with potential anti-tumor properties.